A novel method to measure steroid hormone concentrations in walrus bone from archaeological, historical, and modern time periods using liquid chromatography/tandem mass spectrometry. (6th November 2018) - Charapata, Patrick; Horstmann, Lara; Jannasch, Amber; Misarti, Nicole
Abstract : Rationale: A liquid chromatography/tandem mass spectrometry (LC/MS/MS) method was validated and utilized to measure and analyze four steroid hormones related to stress and reproduction in individual samples from a novel tissue, Pacific walrus ( Odobenus rosmarus divergens, herein walrus) bone. This method determines steroid hormone concentrations in the remote walrus population over millennia from archaeological (>200bp ), historical (200–20bp ), and modern (2014–2016) time periods. Methods: Lipids were extracted from walrus bone collected from these periods using methanol before LC/MS/MS analysis. Isotopically labeled internal standards for each target hormone were added to every sample. Analytical and physiological validations were performed. Additionally, a tissue comparison was done among paired walrus bone, serum, and blubber samples. A rapid resolution liquid chromatography system coupled to a QqQ mass spectrometer was used to analyze all samples after derivatization for progesterone, testosterone, cortisol, and estradiol concentrations. Multiple reaction monitoring was used for MS analysis and data were acquired in positive electrospray ionization mode. Results: Progesterone, testosterone, cortisol, and estradiol were linear along their respective standard calibration curves based on their R 2 values (all > 0.99). Accuracy ranged from 93–111% for all hormones. The recovery of extraction, recovery of hormones without matrix effect, was 92–101%. The overall process efficiency of our method for measuring hormones in walrus bone was 93–112%. Progesterone and testosterone concentrations were not affected by reproductive status among adult females and males, respectively. However, estradiol was different among pregnant and non‐pregnant adult females. Overall, steroid hormones reflect a long‐term reservoir in cortical bone. This method was also successfully applied to walrus bone as old as 3585bp . Conclusions: LC/MS/MS analysis of bone tissue (0.2–0.3 g) provides stress and reproductive data from elusive walruses that were alive thousands of years ago. Based on physiological validations, tissue comparison, and published literature, steroid hormone concentrations measured in walrus cortical bone could represent an accumulated average around a 10–20‐year time span. By investigating how stress and reproductive physiology may have changed over the past ~3000 years based on bone steroid hormone concentrations, this method will help answer how physiologically resilient walruses are to climate change in the Arctic.